Inklusi Keuangan Dalam Hubungannya Dengan Pertumbuhan UMKM Dan Tingkat Kesejahteraan Masyarakat Di Palangkaraya, Kalteng - Meta Melinda Aldis; Lala Lala; Yomelin Andini; Larissa K.T.T. Situmorang; Riki Cahyadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research explores the impact of financial inclusion on the growth of Micro, Small and Medium Enterprises (MSMEs) in Central Kalimantan, Indonesia, during the 2011-2021 period. Data analysis shows an increase in financial services account ownership from 20% to 52%, contributing to economic growth and a decrease in the unemployment rate. This study highlights the role of government policy in promoting access to financial and supporting services for MSMEs, which is crucial in developing local economies and social welfare. The implications of these findings recommend strengthening financial inclusion policies and increasing support for MSMEs to optimize economic growth and expand employment opportunities in Central Kalimantan.